Women-led agroforestry and clean cookstoves in Honduras: Field evaluation of farmer-led gender-transformative strategies for low emissions agriculture - Hottle, R. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This paper outlines the development of a women-led agroforestry and improved cookstoves project in Honduras. Analysis aims to contribute to learning for future projects, especially projects aiming to improve gender relations. The project intended to increase gender equity among smallholder farmers while reducing greenhouse gas emissions through agroforestry and fuel-efficient stoves. The project was successful due to a) participating farmers’ experience with innovation and research; b) engagement of men in women-led activities to enable slow, organic changes in gender relations within the implementing organization, farmers’ organizations and households; and c) the strong history, knowledge and working relations that the implementing organization had with farmers on the ground. Areas for improvement include harnessing farmers’ knowledge of crop breeding and research to test a wider range of coffee varieties under different conditions, and improving data collection systems. Main technical findings cover topics from micro-catchment to integrated pest management to micro- financing. This report includes an explanation of the community’s needs; a description of the technical, social, scientific and economic innovations employed in the execution of the project; and a series of recommendations to aid in the development of future projects.